2014
DOI: 10.1055/s-0034-1384816
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Aid Use and Adherence to Treatment in a Publicly-Funded Health Service from the City of São Paulo, Brazil

Abstract: Introduction Periodic follow-up appointments are important to ensure long-term effectiveness of rehabilitation with hearing aids. However, not all users are able to maintain adherence to recommendations prescribed during the fitting process and some do not attend those appointments, which compromises the effectiveness of treatment. Objective Compare hearing aid use after 1 year between subjects who did not attend a follow-up evaluation appointment at a publicly-funded health service (nonattenders) and those wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Adherence tends to be lower in patients over 80 years old who use bilateral devices [ 12 ]. A long time of use of the device is associated with more daily use [ 26 , 30 , 31 , 32 , 35 ]. Studies have shown that a longer duration of device use is associated with increased daily usage [ 26 , 30 , 31 , 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adherence tends to be lower in patients over 80 years old who use bilateral devices [ 12 ]. A long time of use of the device is associated with more daily use [ 26 , 30 , 31 , 32 , 35 ]. Studies have shown that a longer duration of device use is associated with increased daily usage [ 26 , 30 , 31 , 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A long time of use of the device is associated with more daily use [ 26 , 30 , 31 , 32 , 35 ]. Studies have shown that a longer duration of device use is associated with increased daily usage [ 26 , 30 , 31 , 32 , 35 ]. Maul et al support these findings and assert that approximately half of the patients prescribed hearing aids do not utilize them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations